Prisoners and cigarettes or 'imprisoned in cigarettes'? What helps prisoners quit smoking? - Makris Elias; Gourgoulianis Konstantinos I; Hatzoglou Chrysi (BMC, 2012)
Abstract Background The aim of the study was, despite the special characteristics of prisons, to identify the features which led prisoners who attended the Smoking Cessation Centre at the Kassavetia Detention Centre in Volos (region of Thessaly, in the central part of mainland Greece) to quit smoking. Methods Personal interviews with 204 male prisoners irrespective of smoking habitus over the period June 2008 to December 2010 were obtained. Information about medical history, history of tobacco use and addiction to narcotic use was obtained and imprisonment status was recorded. Pharmaceutical treatment (Varenicline) and counselling or only counselling were suggested as alternative strategies to them in order to help quit smoking. SPSS v15.0 software was employed, descriptive statistics were used, and a X2 independence test and Student's t-test were performed. Results Of the sample examined, 75.5% (154) were smokers. They were mainly Greeks (51.5%), single (53.4%) and had not gratuated from a high school (secondary education level) (70.6%). 59.75% begun smoking early ( ≤14 years of age ) and 64.9% were highly addicted according to Fagerstrom Tolerance Questionnaire. 74% (114) of all smokers at the prison attended the Smoking Cessation Centre. Of them, 30.7% were able to quit smoking at 3 months but 1 year later there were 20.2% ex-smokers. The key characteristics of those who were able to be ex-smokers were a change in smoking habits (decreased) compared to when free (p = .001), previous attempts to quit (while incarcerated and in general) (p = .001), average dependence levels (p < .001), started smoking after 21 years of age (p = .032), no history of addictive substance use (p = .029), being already prisoners for a longer period of time (p = .019), a limited number (3.9 ± 3.4) of prisoners per cell (p < .001) and in particular a limited number (2.8 ± 3.2) of smokers in the cell (p < .001). Conclusions Average dependence, a past free of addictive substance abuse and a better environment of daily living for certain prisoners (as far as the number of cellmates was concerned) had a catalytic impact on prisoners finally managed to quit smoking.